The Power and Roots of Aspirations : A Survey of the Empirical Evidence - Fruttero, Anna; Muller, Noel; Calvo-Gonzalez, Oscar (World Bank, Washington, DC, 2021)
Aspirations have become a common theme in empirical economics studies, but there is no unified understanding of the range of outcomes they influence, the factors that shape them, and how to measure them. This paper surveys this growing literature. The paper argues that there is compelling evidence to consider aspirations as a useful lens to analyze human behavior and development outcomes, at the individual and aggregate levels, in poorer and richer countries. The empirical evidence aligns with the theory that high aspirations can lead individuals to achieve better educational, labor market, and other outcomes and can contribute to making countries more equal and prosperous. The empirical evidence also confirms that the mix of social and circumstantial factors shaping aspirations tends to hinder the aspirations of the disadvantaged—such as the poor, immigrants, and women—and can contribute to vicious circles of poverty, high inequality, low social mobility, and low growth. However, high aspirations should not be considered as an end in themselves as they can backfire, with deleterious effects, if unmatched with opportunities. Further, the paper argues that definitional and measurement issues can affect the understanding of the topic and that studies should more explicitly describe their measures of aspirations to ensure that divergent underlying concepts are not mistaken.